Study on sensing properties of chitosan-polyethylene oxide-exfoliated graphite based toluene sensors / \c Aisha Elhadi Ali Abosnina. - Elhadi Ali Abosnina, Aisha (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
The main objectives of this research are ; to study the effect of polyethylene oxide (PEO) on morphology and electrical properties of chitosan film ; to study the effect of exfoliated graphite (EG) on morphology and electrical properties of chitosan/polyethylene oxide films ; to study the sensing properties of chitosan/polyethylene oxide/exfoliated graphite films toward toluene.